Involvement of Long‐Lived Intermediate States in the Complex Folding Pathway of the Human Telomeric G‐Quadruplex1. Issue 29 (2nd June 2015) - Bessi, Irene; Jonker, Hendrik R. A.; Richter, Christian; Schwalbe, Harald
Abstract The energy landscapes of human telomeric G‐quadruplexes are complex, and their folding pathways have remained largely unexplored. By using real‐time NMR spectroscopy, we investigated the K+‐induced folding of the human telomeric DNA sequence 5′‐TTGGG(TTAGGG)3A‐3′. Three long‐lived states were detected during folding: a major conformation (hybrid‐1), a previously structurally uncharacterized minor conformation (hybrid‐2), and a partially unfolded state. The minor hybrid‐2 conformation is formed faster than the more stable hybrid‐1 conformation. Equilibration of the two states is slow and proceeds via a partially unfolded intermediate state, which can be described as an ensemble of hairpin‐like structures.